PENGARUH STRECHING SETELAH AKTIVITAS AEROBIK TERHADAP DENYUT NADI ISTIRAHAT PEMAIN FUTSAL SMAN 1 JENEPONTO - Kurniawan Kurniawan; Etno Setyagraha; Wahyudin Wahyudin (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2022)
The purpose of this study was to determine whether there was an effect of stretching after aerobic activity on the resting heart rate of SMA 1 Jeneponto futsal players. The research subjects in this study were futsal athletes, totaling 10 male athletes. This research is an experimental research. The instrument used to measure and obtain responses from abilities, performance, behavior of samples or objects in data collection for stretching tests after aerobic activity on pulse from Sulistiyono (2017). The data collection technique uses tests and measurements. . Data analysis techniques using SPSS using descriptive analysis, normality test, T test. Based on the results of the data and discussion from this study it can be concluded that there is an effect of stretching after aerobic activity on the resting pulse of futsal players. From the data of the active stretching group, the pre-test value obtained an average pulse rate of 107.5. the post-test value obtained an average pulse value of 92.2. P value of 0.001 (p <0.05) thus there is an effect of active stretching on the decrease in pulse rate of SMA 1 futsal players Jeneponto